Synthesis and Biological Evaluation of HDAC Inhibitors With a Novel Zinc Binding Group - He, Junquan; Wang, Songsong; Liu, Xingang; Lin, Ruili; Deng, Fang; Jia, Zhong; Zhang, Chenghong; Li, Zhao; Zhu, Hongtian; Tang, Lei; Yang, Pingrong; He, Dian; et al. (Frontiers in Chemistry, 2020)
Vorinostat (SAHA) is the first HDACs inhibitor approved by the FDA for the treatment of cutaneous T-cell lymphoma, and the broad-spectrum inhibitory activities towards HDAC families make SAHA exhibit great therapeutic potential. However, the drawbacks associated with hydroxamic acid group (poor stability, easy metabolism, weak binding ability to class Ⅱa isozymes, and poor selectivity) have been exposed during the process of the continuous clinical application, making the discovery of HDAC inhibitors with novel zinc binding group (ZBG) more necessary. Based on the pharmacophore of HDAC inhibitors, two novel classes of compounds were designed and synthesized by replacing the hydroxamate with new groups, and the antitumor activities were evaluated in four human cancer cell lines (A549, Hela, HepG2, and MCF-7). Among the target compounds, compounds a6, a9, a10, b8, and b9 exhibited better inhibitory activities against the selected tumor cell lines, such as Hela and A549, and their biological activities were further verified through enzyme inhibition experiments, showing that compounds a9 and b8 had certain enzyme inhibitory activities (a9: IC50 = 5.5 µM; b8: IC50 = 22.5 µM). In addition, the Western blot results showed that compound a9 could only promote the acetylation level of HDAC6 substrates, and a9 promoted the acetylation levels of HDAC Ⅰ and HDAC6 substrates, indicating that compound b8 had certain selective inhibitory activities. Moreover, the inhibitory mechanism of compound a9 and b8 were compared through computational approaches, and compound a9 and SAHA had similar binding patterns in HDAC1. In summary, the compounds with novel ZBG exhibited certain antitumor activities, providing valuable hints for the discovery of novel HDAC inhibitors.